1988
DOI: 10.1021/bi00417a055
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative 4-dechlorination of polychlorinated phenols is catalyzed by extracellular fungal lignin peroxidases

Abstract: The extracellular lignin peroxidases (ligninases) of Phanerochaete chrysosporium catalyzed HzOz-dependent spectral changes in several environmentally significant polychlorinated phenols: 2,4-dichloro-, 2,4,5-trichloro-, 2,4,6-trichloro-, and pentachlorophenol. Gas chromatography/mass spectrometry of reduced and acetylated reaction products showed that, in each case, lignin peroxidase catalyzed a 4-dechlorination of the starting phenol to yield a p-benzoquinone. The oxidation of 2,4-dichlorophenol also yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(108 citation statements)
references
References 36 publications
11
97
0
Order By: Relevance
“…In the case of the SBP/H 2 O 2 system, any other intermediate was identified, but the reaction mixture initially turns from colourless to yellow, indicating the probable production of 2,6-dichloro-1,4-benzoquinone, in agreement with previous data reported for the reaction catalyzed by lignine peroxidase [30] and horseradish peroxidase [31].…”
Section: System Dispersed In Aqueous Solutionsupporting
confidence: 90%
“…In the case of the SBP/H 2 O 2 system, any other intermediate was identified, but the reaction mixture initially turns from colourless to yellow, indicating the probable production of 2,6-dichloro-1,4-benzoquinone, in agreement with previous data reported for the reaction catalyzed by lignine peroxidase [30] and horseradish peroxidase [31].…”
Section: System Dispersed In Aqueous Solutionsupporting
confidence: 90%
“…Both enzymes oxidized 2,4-dichlorophenol (I) to 2-chloro-1,4-benzoquinone (II). The LiP oxidation of 2,4-dichlorophenol (I) to this product has been previously reported (17). However, the results shown in Fig.…”
Section: Resultsmentioning
confidence: 51%
“…The irregular and recalcitrant nature of lignin and the fact that it contains substructures found in primary pollutants such as phenols, anisoles, biphenyls, and diarylethers led researchers to postulate that the nonspecific ligninolytic system produced by white rot fungi might be capable of oxidatively degrading persistent aromatic pollutants (2,3,16 nols (19,27). In addition, previous work (17,27) demonstrated that LiP could catalyze the first oxidative dechlorination step in the degradation of several chlorinated phenols. However, except for this initial step, fungal chlorophenol degradative pathways have not been previously elucidated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…strain DABAC 1, likely due to a partial dehalogenation of chlorinated contaminants. This was not surprising since both lignin peroxidase and laccase have been shown to be able to catalyze the oxidative dechlorination of both chlorophenols and chloroanilines (17,28).…”
Section: Discussionmentioning
confidence: 96%